Fabric design identity: implementation of pattern formation into kain punca potong ( KPP ) weaving design - Ahmad, Nani Hartina; Shaari, Nazlina; Mohd Ali, Noor Azizi; Abd Latif, Muhammad Pauzi (Science & Engineering Research Support Society, 2019)
Kain punca potong (KPP) is a long fabric generally crafted via the ikat technique resulting in square patterns with striped motifs consisting of a decorative limar pattern. Instead of decorative motifs and KPP design, this paper will embark on a discourse on pattern formation style specific to the design style and pattern composition of KPP motifs, design and use in Malay society. The paper shows that this textile provided some valuable insights into Malay culture and fabric identity. Regarding the Malay textile context, the main issue revolves around local textile‟s Malay fabric identity pattern formation. This issue came to be when it was discovered that other communities lack awareness when it comes to understanding the fabric identity of Malay textiles, let alone its fabric design identity. This paper also provides enhanced deliberation on the use of pattern formation basis inspired by design style consisting of selected motifs and pattern composition to identify the identity of fabric design. The researcher used qualitative approach to identify the attributes of fabric design identity, which included pattern formation and style process. This paper will therefore seek to uncover viable concepts and techniques that passed as feasible guidelines for new designers when incorporating a "distinctive" national identity in their design. For this study, in addition to interviews, fieldwork notes, photography and video documentation, participant observation in the form of a master weaver apprenticeship will aid better understanding of weaving design learning process while participation in design education will provide insights on how design knowledge is transmitted. It also explores the potential of pattern formation style to further develop the identity of fabric design in various design forms, particularly in the field of textile weaving design.